SOCIO-ECONOMIC IMPACT ON SUSTAINABLE MOUNTAIN TOURISM OF GEORGIA (World Science, 2021)
Tourism has a range of impacts on mountain ecosystems, communities and economies. Many of these impacts are negative, but tourism may also generate positive impacts. They can become supportive force for maintaining peace, fostering pride and cultural traditions, creating local jobs, increasing visitor awareness of natural, cultural and historical values and assets. Local communities and businesses support the long-termsustainability of a tourism destination. A decrease in cultural diversity or authenticity and loss of local customs and traditions may bring the destination to the loss of the attractiveness to visitors seeking a unique cultural experience and attractiveness. In one of the mountain regions of Georgia – Svaneti - the economic benefits of tourism are channeled into the local economy of the region i.e. local community benefit from tourism activities and local businesses (accommodation, transport, food and beverages outlets, souvenirs and crafts etc.) contribute to the authentic nature of the particular mountain destination. Cross-cultural awareness, communication between visitors and local people raises the quality of visitor experience and the level of community understanding in support of tourism.